Allele frequencies and other forensic parameters of the HID-Ion AmpliSeq™ Identity Panel markers in Basques using the Ion Torrent PGM™ platform. (May 2017) - García, O.; Soto, A.; Yurrebaso, I.
Highlights: We conducted a forensic population genetics investigation in 105 Basques. The results suggested that the HID-Ion AmpliSeq™ Identity Panel is a well-performed, reliable and high informative assay. The HID-Ion AmpliSeq™ Identity Panel is a very promising tool for paternity testing and human identification in the forensic field. All loci were in Hardy-Weinberg equilibrium with no association between them. Forensic parameters were calculated as 5.74 × 10 −36 for combined match probability and 99.99998% for combined power of exclusion. Abstract: The HID-Ion AmpliSeq™ Identity Panel amplifies 90 autosomal SNPs and 34 Y- SNPs with massively parallel sequencing (MPS) using the Ion Torrent PGM™ platform. In the present study, 105 Basques were analyzed to assess this panel. All loci were in Hardy-Weinberg equilibrium and no association between them was detected. Forensic parameters were calculated as 5.74 × 10 −36 for combined match probability and 99.99998% for combined power of exclusion. In conclusion, the HID Identity panel and the use of this new MPS technology are very promising tools for paternity testing and human identification in routine casework in the forensic field.